2023
DOI: 10.1073/pnas.2209037120
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of a marine keystone predator transforms terrestrial predator–prey dynamics

Abstract: Sea otters ( Enhydra lutris ) and wolves ( Canis lupus ) are two apex predators with strong and cascading effects on ecosystem structure and function. After decades of recovery from near extirpation, their ranges now overlap, allowing sea otters and wolves to interact for the first time in the scientific record. We intensively studied wolves during 2015 to 2021 in an island system colonized by sea otters in the 2000s and by wolves in 2013. After wolf colonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…For instance, the conservation of wolves in Yellowstone National Park led to the recovery of willow trees and the return of beavers, which in turn drastically affected stream ecosystems (35). On island systems, such as in the case of the sea otter-wolf relationship (7), the consequences can be severe and drive the relatively small local populations to near extinction, as seen in our study. Therefore, management actions that are meant to conserve a specific species need to be carefully assessed to determine how interactions with other species will be affected (37).…”
Section: The Trade-offs In Sea Turtle Conservationmentioning
confidence: 59%
See 2 more Smart Citations
“…For instance, the conservation of wolves in Yellowstone National Park led to the recovery of willow trees and the return of beavers, which in turn drastically affected stream ecosystems (35). On island systems, such as in the case of the sea otter-wolf relationship (7), the consequences can be severe and drive the relatively small local populations to near extinction, as seen in our study. Therefore, management actions that are meant to conserve a specific species need to be carefully assessed to determine how interactions with other species will be affected (37).…”
Section: The Trade-offs In Sea Turtle Conservationmentioning
confidence: 59%
“…In the case of Orchid Island, numerous species were affected due to their general susceptibility to the top snake predators. These top-down effects operating through the interaction between marine subsidies and generalist predators may be more widespread in nature than is generally appreciated [e.g., (6)(7)(8)11)]. For instance, a recent study showed that the proliferation of wolves because of previously unavailable marine prey (sea otters) drove the extinction of terrestrial ungulates on an island (7).…”
Section: The Oceanic Subsidy-generalist Predator Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Predator-prey interactions on Coronation Island (above) and Pleasant Island (below); from Roffler et al (2023) [1]; CC BY-NC-ND 4.0.…”
Section: Figurementioning
confidence: 99%
“…It is observed that a wolf population would die of starvation when their primary prey -often ungulates -disappeared. However, for the wolves on Pleasant Island of Alaska, when "running out" of deer, they switched to feeding on sea otters instead (Roffler et al, 2023). This change in primary diet and hunting strategy basically turned these apex predators into "sea wolves", driven by fundamental survival desire (Le, 2023).…”
mentioning
confidence: 99%